1987
DOI: 10.1017/s0022029900025395
|View full text |Cite
|
Sign up to set email alerts
|

Formation of volatile aroma compounds and carbon dioxide in yogurt starter grown in cows' and goats' milk

Abstract: SummaryYogurt starter B3 was grown in cows' milk, goats' milk I (obtained 2–3 weeks after parturition) and goats' milk II (8 months after parturition), and a number of biochemical and bacteriological parameters were recorded at intervals during incubation for 8 h at 43°C. No appreciable differences between the milks were observed for total viable count, bacteriological ratio of rods to cocci, or decrease in pH. Production of acetaldehyde, however, was considerably lower in goats' milk I (6·2 ppm) and goats' mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
25
1
1

Year Published

1994
1994
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 12 publications
8
25
1
1
Order By: Relevance
“…This could be attributable to the high mean content (5.1 µg  g -1 ) of diacetyl (data shown in the previous paper) when compared with threshold in water (0.2 µg  g -1 ) (Molimard and Spinnler 1996). This finding is in agreement with the report by Rysstad and Abrahamsen (1987). The presence of diacetyl is thought to contribute to the delicate, full flavor and aroma of yoghurt, and their presence are important if acetaldehyde content is low (Beshkova et al 1998).…”
Section: Results and Discusionsupporting
confidence: 92%
“…This could be attributable to the high mean content (5.1 µg  g -1 ) of diacetyl (data shown in the previous paper) when compared with threshold in water (0.2 µg  g -1 ) (Molimard and Spinnler 1996). This finding is in agreement with the report by Rysstad and Abrahamsen (1987). The presence of diacetyl is thought to contribute to the delicate, full flavor and aroma of yoghurt, and their presence are important if acetaldehyde content is low (Beshkova et al 1998).…”
Section: Results and Discusionsupporting
confidence: 92%
“…The amounts of each constituent were determined by the Pearson Square Method as described before [16,17]. Gelatine stabilizer (0.25%, w/v) sourced from Leiner Davis Gelatine SA Krugersdorp was also added at 40 o C as described before [18] C and was stopped when the pH (Hyperscan model 510 pH meter) was 4.6.…”
Section: Production Of Yoghurtmentioning
confidence: 99%
“…al. 1978, Rysstand and Abrahamsen 1987, Yaygın and Mehanna 1988. Hence, the results of this study showed that if the amount of acetaldehyde is in a certain range, it positively affects the aroma and flavour of strained yoghurt.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Görner et al (1973) stated that a level of 10-20 mg kg -1 acetaldehyde was required for the optimum flavouraroma, while Rasic and Kurman (1978) reported that 21-41 mg kg -1 of acetaldehyde was necessary for the typical flavour and aroma in yoghurt. In contrast to this, the level of acetaldehyde in set yoghurt from goat milk was obtained as 4.5-5.5 mg kg -1 by Abrahamsen et al (1978), 6.2-8.9 mg kg -1 by Rysstand and Abrahamsen (1987), an average of 9.7 mg kg -1 by Yaygın and Mehanna (1988), 1.5-9.0 mg kg -1 by Wojtowski et al (1995) and 3.19-3.96 mg kg -1 by Karademir et al (2001). The low level of acetaldehyde could be attributed to the relatively high concentration of glycine in goat milk, which can inhibit enzymes involved in the conversion of threonin to acetaldehyde (Peaker et al 1981, Tamime andRobinson 1999).…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation